Personal-Social Adjustment Counseling for Indonesian Migrant Workers Experiencing Reverse Culture Shock After Overseas Employment - Husnul Hafidhoh; Alifa Suri Rahmadhina Rahmadhina (P3M STAI Kuningan, 2024)
Background: Indonesian migrant workers returning from overseas employment face profound psychosocial challenges during reintegration, yet systematic counseling support remains critically absent within national migration governance frameworks.Objective: This study aimed to explore personal-social adjustment difficulties experienced during reverse culture shock and develop an evidence-based counseling intervention model tailored to Indonesian cultural contexts.Method: An explanatory sequential mixed-methods design was employed, involving quantitative surveys with 187 returned migrant workers from East Java, Central Java, and West Nusa Tenggara.Findings and Implications: Findings revealed that 67.4% of returnees experienced severe adjustment difficulties across four interconnected dimensions: identity fragmentation, family relationship disruption, economic vulnerability, and social alienation, with these challenges operating as a self-reinforcing system undermining sustainable reintegration. Conclusion: This research represents the first comprehensive, theoretically grounded counseling intervention specifically designed for Indonesian returned migrant workers experiencing reverse culture shock, filling a critical gap in both scholarship and practice by integrating evidence-based psychological principles with indigenous Indonesian cultural values, Islamic spiritual perspectives, and community-based support systems, thereby establishing a replicable model for psychosocial reintegration services that can be systematically implemented across Indonesia's migrant-sending regions through government agencies, NGOs, and community institutions.